Pengaruh Kesadaran, Pengetahuan, dan Sanksi terhadap Kepatuhan Wajib Pajak Orang Pribadi - Endang Sri Apriani; Apriyani Dwi Lestari; Sisca Santika; Hendra Sanjaya Kusno (Akuisisi : Jurnal Akuntansi, 2025)
Tax is the main source of state revenue that is important to support national development and the progress of the country. In 2023, there was a fluctuation in tax revenue in Indonesia. Although there was an increase in the submission of Annual Tax Returns from 2020 to 2022, the increase was not optimal. This study aims to examine the effect of tax awareness, tax knowledge, and tax sanctions on individual taxpayer compliance at PT PLN NUSA DAYA in Balikpapan City. Using quantitative methods and Statistical Product and Service Solutions software, data from 60 employee respondents registered at PT PLN NUSA DAYA were taken through saturated sampling techniques. The results of the study indicate that tax awareness, tax knowledge, and tax sanctions simultaneously affect taxpayer compliance. Partially, tax awareness and tax knowledge have a positive effect on individual taxpayer compliance, while tax sanctions have no effect. Further researchers can add other variables. Variable variables are expected to find things that can increase individual taxpayer compliance.